FOOD AND NUTRITION SECURITY IN SOUTHERN HONDURAS IN 2022: A STUDY FROM TERRITORIAL AND FAMILY DYNAMICS (REMUNOM, 2026)
Food and Nutrition Security (FNS) in Honduras faces persistent challenges, particularly in the southern region, where households experience multiple vulnerability factors, including socioeconomic constraints, unequal access to resources, and exposure to natural disasters. This article analyzes FNS among households in the southern part of the country, focusing on food consumption patterns, dietary diversity, and factors conditioning food vulnerability. A mixed-method approach was employed using secondary data from the National Institute of Statistics (INE) and other official sources, applying the CARI methodology, which allows classification of FNS based on food consumption, dietary diversity, economic vulnerability, and coping strategies in response to food scarcity. The sample included 499 households. The results show that 16% of households achieved food security, 53% presented marginal food security, 30% experienced moderate food insecurity, and 1% were in severe food insecurity, indicating that more than half of households are in a vulnerable condition that limits access to adequate and stable food. Dietary analysis revealed a dependence on fats, carbohydrates, and sugars, with low consumption of fruits, roots, and other micronutrient-rich foods, suggesting potential deficiencies in vitamins, fiber, and minerals. Although the consumption of animal- and plant-based proteins was relatively high, the regular intake of iron and other critical micronutrients was insufficient. Households present structural vulnerabilities, including low educational attainment of household heads and limited access to basic services such as safe drinking water, sanitation, and improved energy sources. These conditions directly affect the capacity to maintain healthy and diversified diets. It is concluded that, despite general access to food, nutritional imbalances and socioeconomic vulnerabilities persist, highlighting the need to strengthen public policies and comprehensive sustainable FNS strategies, incorporating interventions in education, health, infrastructure, and food diversification, in line with PyENSAN 2030 and the Sustainable Development Goals.